2023
DOI: 10.1002/advs.202204194
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase 4/Midline‐1 Axis Promotes T Lymphocyte Motility in Atherosclerosis

Abstract: T cells play a crucial role in atherosclerosis, with its infiltration preceding the formation of atheroma. However, how T‐cell infiltration is regulated in atherosclerosis remains largely unknown. Here, this work demonstrates that dipeptidyl peptidase‐4 (DPP4) is a novel regulator of T‐cell motility in atherosclerosis. Single‐cell ribonucleic acid (RNA) sequencing and flow cytometry show that CD4+ T cells in atherosclerotic patients display a marked increase of DPP4. Lack of DPP4 in hematopoietic cells or T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Cytoskeletal rearrangement plays a crucial role in cell migration 34 and we have reported that Mid1 deletion results in disrupted cytoskeletal rearrangement and migration 24 . However, the mechanism via which Mid1 regulates cytoskeletal rearrangement and cell migration is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytoskeletal rearrangement plays a crucial role in cell migration 34 and we have reported that Mid1 deletion results in disrupted cytoskeletal rearrangement and migration 24 . However, the mechanism via which Mid1 regulates cytoskeletal rearrangement and cell migration is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Mid1 -/- mice were generated using CRISPR-Cas9 technology as we previously described 24 . Rag2 -/- and CD45.1 mice were purchased from Shanghai Model Organisms Center, Inc. All the mice used in the experiment were kept in the SPF animal facilities at Tongji Hospital.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DPP4+ chimeric antigen receptor T cells exhibited robust cytotoxicity against the DPP4+ T-cell lymphoma cells activated multiple effector functions and limited tumour progression (22). However, DPP4 de ciency reduces T-cell motility by suppressing the expression of microtubule associated protein midline-1 in T cells (23). Post-translational modi cation of chemokines mediated by DPP4 has been shown to negatively regulate lymphocyte tra cking, and its inhibition enhances T cell migration and tumor immunity (24).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases (CVDs) are the leading cause of global mortality and disability, accounting for almost half of total death annually. Atherosclerosis (AS) is an inflammation-driven chronic disease caused by the asymptomatic buildup of plaques on the arterial wall to the formation of atherosclerotic plaque, even the rupture of plaque. , Meanwhile, macrophages play a critical role in uptaking the oxidized low density lipoprotein (ox-LDL) to deteriorate into the foam cells, simultaneously releasing various inflammatory factors and then inducing the formation of atherosclerotic plaque. , Clinical study has found that the foam cell-rich atherosclerotic plaque is prone to rupture into thrombus, inducing some fatal complications such as myocardial infarction and stroke. , Thence, it is highly important to efficiently recognize the foam cells and then precisely identify the morphology and disperse distribution of the plaques for physicians to make timely clinical decisions and perform proactive interventions as early as possible …”
Section: Introductionmentioning
confidence: 99%